Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-02942-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Real-Time Changes in Working Memory Updating and Gating with the Event-Based Eye-Blink Rate

Abstract: Effective working memory (WM) functioning depends on the gating process that regulates the balance between maintenance and updating of WM. The present study used the event-based eye-blink rate (ebEBR), which presumably reflects phasic striatal dopamine activity, to examine how the cognitive processes of gating and updating separately facilitate flexible updating of WM contents and the potential involvement of dopamine in these processes. Real-time changes in eye blinks were tracked during performance on the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 57 publications
4
36
0
Order By: Relevance
“…There is indeed evidence that L-tyrosine can modulate noradrenaline activity, as it has affected the P300 event-related potential (Kishore et al, 2013), a putative marker of phasic noradrenaline activity in the locus coeruleus (Nieuwenhuis, Aston-Jones, & Cohen, 2005). Although the present findings are remarkably consistent with studies that related gate switching in the reference-back task to a dopaminergic marker (Rac-Lubashevsky, Slagter, & Kessler, 2017) and activity in BG (Nir-Cohen et al, 2019), an explanation of the present results in terms of noradrenaline cannot be definitively ruled out. Future research therefore should include and control for measures of noradrenaline activity, for example pupil dilation (Joshi, Li, Kalwani, & Gold, 2016;Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014;Reimer et al, 2016) or salivary alpha amylase levels (Warren et al, 2019;Warren, van den Brink, Nieuwenhuis, & Bosch, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…There is indeed evidence that L-tyrosine can modulate noradrenaline activity, as it has affected the P300 event-related potential (Kishore et al, 2013), a putative marker of phasic noradrenaline activity in the locus coeruleus (Nieuwenhuis, Aston-Jones, & Cohen, 2005). Although the present findings are remarkably consistent with studies that related gate switching in the reference-back task to a dopaminergic marker (Rac-Lubashevsky, Slagter, & Kessler, 2017) and activity in BG (Nir-Cohen et al, 2019), an explanation of the present results in terms of noradrenaline cannot be definitively ruled out. Future research therefore should include and control for measures of noradrenaline activity, for example pupil dilation (Joshi, Li, Kalwani, & Gold, 2016;Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014;Reimer et al, 2016) or salivary alpha amylase levels (Warren et al, 2019;Warren, van den Brink, Nieuwenhuis, & Bosch, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Some previous work suggested that DA phasic activity relates to Bgo^processes Bthat increase the selective updating of contextual features that are relevant for ongoing goal-directed behavior^ (Westbrook & Braver, 2016). In the probe period, we found no differences between trial types, indicating that the different probes may have not imposed different demands on the updating of working memory (Rac-Lubashevsky et al, 2017). While the underlying processes for the pattern of blink rates within each condition may be complex, a clear finding of our analysis is an absence of differential modulation of task-evoked blinks for the different groups, suggesting that dopamine-related updating is not involved in the differences between the different types of behavior.…”
Section: Discussionmentioning
confidence: 40%
“…This gating mechanism is thought to be mediated by phasic dopaminergic activity (Badre & Nee, 2017;Braver & Cohen, 2000;Frank, Loughry, & O'Reilly, 2001;Rougier, Noelle, Braver, Cohen, & O'Reilly, 2005). A recent study found that task-related eye blink rate was associated with efficiency of working memory updating, which according to the authors reflected gating signals released by phasic dopaminergic activity (Rac-Lubashevsky, Slagter, & Kessler, 2017;Tharp & Pickering, 2011). Also, dorso-lateral prefrontal cortex (dlPFC) is causally involved in representing the currently relevant context (Nee & Brown, 2012), and the dopaminergic system is involved in gating an update signal to the dlPFC (D'Ardenne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…EOG has various applications including brain and sleep studies, assistive technology, sleep and mental disorder diagnosis, and HMIs. [45][46][47][48][49] EOG along with electroencephalogram (EEG) and electromyogram (EMG) are used for patients suffering from neural system disorders such as progressive neuro-motor degenerative diseases. However, compared with EEG and EMG, EOG has two major advantages.…”
Section: Introductionmentioning
confidence: 99%